Kleben abzeichnungsfreier Leichtbaustrukturen durch Prozeß-, Gestalt- und Klebstoffoptimierung - Hahn, O.; Eis, M.; Meschut, Gerson (Tagungsband zum 6. Paderborner Symposium Fügetechnik)

Bridging the gap between distributed shared memory and message passing - Karl, Holger (Concurrency - Practice and Experience)

Nerode, Anil, “An Appreciation of Kreisel”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 81–88 - Peckhaus, Volker (zbMATH Open, Zbl. 0895.01006)

Huber-Dyson, Verena, “Toughts on the Occasion of Georg Kreisel’s 70th Birth-day”, in: P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 51–73 - Peckhaus, Volker (zbMATH Open, Zbl. 0895.01011)

VIPspace - A Visually Programmable Shared Workspace - Dücker, M.; Müller, Wolfgang; Rubart, Jessica (Proceedings. 1998 IEEE Symposium on Visual Languages)
With the wide availability of network supporting hard-and software cooperative computer-based environments became extremely popular. A wide range of CSCW (Computer Supported Cooperative Work) tools with video conferencing, electronic mail, shared whiteboards, discussion forums, and shared information systems are already part of daily business. In contrast to the unstructured linear stream of information in electronic mails shared workspaces provide structured administration of electronic information like documents, voice, pictures, and movies. Popular examples of shared workspaces are BSCW (Basic Support for Cooperative Work), Hypernews, Lotus Notes, Alta Vista Forum, Lifelink, Microsoft Exchange and Webshare. Currently, all these systems are not flexible enough to get easily customized to the requirements of the individual application and user only supporting a limited set of predefined different views and functionality. This article introduces VIPspace (Visually Programmable Workspace). VIPspace can be easily customized to the individual needs of an user through VIPrule, a combination of a form- and icon-based visual programming language. VIPrule is based on an easy-to-use drag and drop paradigm. Direct manipulation via drag and drop allows easy access to local file systems as well as manipulation, exchange, and publication of shared multimedia documents. As VIPspace is implemented in Java it nicely integrates with other web-applications and provides a platform independent environment with a uniform graphical user interface.
Keywords: Collaborative work; Electronic mail; Computer networks; Video sharing; Videoconference; Discussion forums; Information systems; Streaming media; Motion pictures; Computer languages

10-Gb/s PMD compensation using deformed-helical ferroelectric liquid crystals - Sandel, D; Hinz, S; Yoshida-Dierolf, M; Graser, J; Noé, Reinhold; Beresnev, L; Weyrauch, T; Haase, W (24TH EUROPEAN CONFERENCE ON OPTICAL COMMUNICATION, VOL 1-3: VOL 1: REGULAR AND INVITED PAPERS; VOL 2: TUTORIALS AND SYMPOSIUM PAPERS; VOL 3: POSTDEADLINE PAPERS)

Influence of polarization on 30 GHz broadband radio channels - Karthaus, U; Noé, Reinhold (1998 INTERNATIONAL ZURICH SEMINAR ON BROADBAND COMMUNICATIONS: ACCESSING, TRANSMISSION, NETWORKING)

SAM - An Animated 3D Programming Language - Geiger, Christian; Müller, Wolfgang; Rosenbach, W. (Proceedings of the IEEE Symposium on Visual Languages)
This article presents the animated visual 3D programming language SAM (Solid Agents in Motion) for parallel systems specification and animation. A SAM program is a set of interacting agents synchronously exchanging messages. The agent's behaviour is specified by means of production rules with a condition and a sequence of actions each. Actions are linearly ordered and execute when matching a rule. In SAM, main syntactic objects like agents, rules, and messages are 3D. These objects can have an abstract and a concrete, solid 3D presentation. While the abstract representation is for programming and debugging, the concrete representation is for animated 3D end-user presentations. After outlining the concepts of SAM this article gives two programming examples of 3D micro worlds and an overview of the programming environment.
Keywords: Animation; Computer languages; Solids; Concrete; Application software; Virtual reality; Programming profession; Switches; Visualization; Debugging

Fiber-based distributed PMD compensation at 20 Gb/s - Noé, Reinhold; Sandel, D; Yoshida-Dierolf, M; Hinz, S; Glingener, C; Scheerer, C; Schopflin, A; Fischer, G (24TH EUROPEAN CONFERENCE ON OPTICAL COMMUNICATION, VOL 1-3: VOL 1: REGULAR AND INVITED PAPERS; VOL 2: TUTORIALS AND SYMPOSIUM PAPERS; VOL 3: POSTDEADLINE PAPERS)

Results of extensive 800 Mb/s, 30 GHz channel sounding experiments - Karthaus, U; Noé, Reinhold (IEEE ANTENNAS AND PROPAGATION SOCIETY INTERNATIONAL SYMPOSIUM - ANTENNAS: GATEWAYS TO THE GLOBAL NETWORK, VOLS 1-4)

Chemisorption of arsenic on InP(110) - Großner, U.; Schmidt, Wolf Gero; Bechstedt, F.; Santos, P.V.; Koopmans, B.; Esser, N. (Surface Science)

Comparison of As-rich and Sb-terminated GaAs(100)(2 × 4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Surface Science)

A Visual Programming Language for Qualitative Data - Dücker, M.; Geiger, Christian; Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C. (Proceedings of the 1997 IEEE Symposium on Visual Languages)
Modeling of human knowledge and reasoning requires the formulation of uncertainty in its various forms. Fuzzy logic was introduced to directly support these applications (H. Zimmermann, 1991). Fuzzy control (FC) which is based on fuzzy logic allows one to control complex systems based on qualitative information like human knowledge (C. Geiger and G. Lehrenfeld, 1994). In fuzzy logic, fuzzy sets are usually defined and manipulated by means of complex mathematics, whereas the fuzzy control process is frequently outlined by visual sketches based on set diagrams in order to enhance the comprehension of the inference process. The rule based execution of this process usually follows the lines of rule based visual programming languages (VPLs), i.e., languages comparable to Agentsheets and ChemTrains. This strongly indicates that VPLs are thus well applicable for this use. We first outline the basic concepts of fuzzy logic and fuzzy control. Thereafter, we sketch a visual language which integrates fuzzy set diagrams in the visual representation of rules. The basic concepts are inherited from the complete visual programming language, Pictorial Janus (PJ). However, we significantly simplify PJ's visual concepts in order to adapt it for our purpose.
Keywords: Computer languages; Fuzzy control; Fuzzy sets; Animation; Visualization; Fires; Application software; Pattern matching; Impedance matching; Domain specific languages

Optical network analyzer applied for fiber Bragg grating characterization - Sandel, D; Noé, Reinhold (IOOC-ECOC 97 - 11TH INTERNATIONAL CONFERENCE ON INTEGRATED OPTICS AND OPTICAL FIBRE COMMUNICATIONS / 23RD EUROPEAN CONFERENCE ON OPTICAL COMMUNICATIONS, VOL 3)

Optical network analyzer applied for fiber Bragg grating characterization - Sandel, D; Noé, Reinhold (IOOC-ECOC 97 - 11TH INTERNATIONAL CONFERENCE ON INTEGRATED OPTICS AND OPTICAL FIBRE COMMUNICATIONS / 23RD EUROPEAN CONFERENCE ON OPTICAL COMMUNICATIONS, VOL 3)

Visual-Textual Prototyping of 4D Scenes - Dücker, M.; Geiger, Christian; Hunstock, R.; Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the 1997 IEEE Symposium on Visual Languages)
3D-graphics are becoming popular in a steadily increasing number of areas such as entertainment, scientific visualization, simulation, and virtual reality. Despite this rapid growth the generation of animated 3D scenes is by no means trivial. Since animated 3D objects evolve over time the authors denote these objects as 4D. The article presents a novel approach to the rapid prototyping of 4D models. They introduce the AAL (Animated Agent Layer) system. AAL is an interpreter-based approach covering a textual (AAL-PR) as well as a visual command language (AAL-VL) for the specification of the dynamics in 4D scenes. AAL provides support for different levels of abstraction: primitives, structured objects, animated objects, and animated (autonomous) agents.
Keywords: Prototypes; Layout; Animation; Command languages; Application software; Libraries; Virtual reality; Computer graphics; Hardware; Context modeling

A Generic System for Interactive Real--Time Animation - Dücker, M.; Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C. (Proceedings International Conference and Workshop on Engineering of Computer-Based Systems)
The authors present a new approach to an interactive design and analysis environment for visual languages. The main components, i.e., editor animator and interpreter are introduced. Their interactions are being investigated emphasizing the interpreter-animator interaction and defining an interface supporting different levels of automation. The interpreter performs the executions on a logical level and triggers the animator. The interactive animation provides a very high degree of liveness since it is based on the tight integration of the animator and editor. The proposed architecture permits the distributed implementation of a system for real-time animation. Their concepts are validated by the implementation of a debugging environment for the complete visual programming language Pictorial Janus.
Keywords: Real time systems; Animation; Debugging; Automation; Computer languages; Timing; Environmental management; Programming environments; Visualization; Multimedia systems

The Influence of Hermann Günther Grassmann and Robert Grassmann on Ernst Schröder’s Algebra of Logic - Peckhaus, Volker (Hermann Günther Graßmann (1809–1877): Visionary Mathematician, Scientist and Neo-humanist Scholar. Papers from a Sesquicentennial Conference)
Rezensionen: Modern Logic 7 (1997), 88 (I.H. Anellis, “Bibliographic Notic-es”); MR 97j:01024 (J.W. Dauben); Zbl. Math. 907.01026 (J.J. Cross).

Automata, Languages and Programming, 23rd International Colloquium, ICALP96

Adatoms and vacancies on the diamond(111) surface - Bechstedt, F; Schmidt, Wolf Gero; Scholze, A (Europhysics Letters (EPL))